Psychological distress among people with probable COVID-19 infection: analysis of the UK Household Longitudinal Study - Claire L. Niedzwiedz; Michaela Benzeval; Kirsten Hainey; Alastair H. Leyland; Srinivasa Vittal Katikireddi (BJPsych Open, 2021)
Studies exploring the longer-term effects of experiencing coronavirus disease-2019 (COVID-19) on mental health are lacking. We explored the relationship between reporting probable COVID-19 symptoms in April 2020 and psychological distress (measured using the General Health Questionnaire) 1, 2, 3, 5 and 7 months later. Data were taken from the UK Household Longitudinal Study, a nationally representative household panel survey of UK adults. Elevated levels of psychological distress were found up to 7 months after probable COVID-19, compared with participants with no likely infection. Associations were stronger among younger age groups and men. Further research into the psychological sequalae of COVID-19 is urgently needed.